Project-based Learning Model to Support 21st Century Learning: Case Studies in Vocational High Schools - Roemintoyo; Budiarto, Mochamad Kamil (LPPM Undiksha, 2023)
Vocational education is one of the educational institutions that has a high concern for producing graduates with superior competence and competitiveness. The variety of competencies needed in the business and industrial world (DUDI) makes institutions such as vocational and vocational schools have to always innovate in order to be able to provide competences that are truly aligned with DUDI needs. One of them is through the application of innovative learning models which are expected to bring effects and changes to the learning climate. This research is to analyze supporting and inhibiting factors in the implementation of Project Based Learning in Vocational Education, and to identify the understanding of some Educators of PjBL both conceptually and practically. This research is included in the type of qualitative research, and will take a sample of 6 (six) teaching staff in vocational schools, with data collection techniques namely interviews, observation, questionnaires and documentation. Research finding data will be analyzed interactively and described to provide an overview of actual field events. Research results prove that project-based learning can run optimally due to the support of all school members, and commitment from teachers in learning activities. Students are also seen to be very active and skilled in completing a given project. Through the application of project-based learning, it is hoped that students can learn actual competencies or skills. It is hoped that through the results of this research, educators and vocational schools can use the project-based learning model (PjBL) as a learning model that is still relevant to the current curriculum implementation.